(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Introduction. This article highlights the importance of C-reactive protein (CRP) and procalcitonin (PCT), and cytokines in determining the prognosis of SARS-CoV-2-associated pneumonia. The article discusses the methods used to measure these biomarkers and the results of studies that have investigated their use in predicting the severity and outcome of SARS-CoV-2-associated pneumonia. The article concludes with a discussion of the implications of these findings and suggestions for future research. Purpose of the study. This study highlights the importance of CRP, PCT, and cytokines such as IL-6 – In determining the prognosis of SARS-CoV-2-associated pneumonia. This discusses the methods used to measure these biomarkers and the results of studies that have investigated their use in predicting the severity and outcome of SARS-CoV-2 – associated pneumonia. The study concludes with a discussion of the implications of these findings and suggestions for future research.